AT 2020wey and the class of faint and fast tidal disruption events - Charalampopoulos P.; Pursiainen M.; Leloudas G.; Arcavi I.; Newsome M.; Schulze S.; Burke J.; Nicholl M. (EDP Sciences, 2025)
We present an analysis of the optical and ultraviolet properties of AT 2020wey, a faint and fast tidal disruption event (TDE) at 124.3 Mpc. The light curve of the object peaked at an absolute magnitude of Mg = −17.45 ± 0.08 mag and a maximum bolometric luminosity of Lpeak = (8.74 ± 0.69)×1042 erg s−1, making it comparable to iPTF16fnl, the faintest TDE to date. The time from the last non-detection to the g-band peak is 23 ± 2 days, and the rise is well described by L ∝ t1.80 ± 0.22. The decline of the bolometric light curve is described by a sharp exponential decay steeper than the canonical t−5/3 power law, making AT 2020wey the fastest declining TDE to date. The multi-band light curve analysis shows first a slowly declining blackbody temperature of TBB ∼ 20 000 K around the peak brightness followed by a gradual temperature increase. The blackbody photosphere is found to expand at a constant velocity (∼1300 km s−1) to a value of RBB ∼ 3.5 × 1014 cm before contracting rapidly. Multi-wavelength fits to the light curve indicate a complete disruption of a star of M⋆ = 0.11−0.02+0.05 M⊙ by a black hole of MBH = 106.46−0.09+0.09 M⊙. Our spectroscopic dataset reveals broad (∼104 km s−1) Balmer and He II 4686 Å lines, with Hα reaching its peak with a lag of ∼8.2 days compared to the continuum. In contrast to previous faint and fast TDEs, there are no obvious Bowen fluorescence lines in the spectra of AT 2020wey. There is a strong correlation between the MOSFIT-derived black hole masses of TDEs and their decline rate. However, AT 2020wey is an outlier in this correlation, which could indicate that its fast early decline may be dictated by a different physical mechanism than fallback. After performing a volumetric correction to a sample of 30 TDEs observed between 2018 and 2020, we conclude that faint TDEs are not rare by nature; they should constitute up to ∼50–60% of the entire population and their numbers could alleviate some of the tension between the observed and theoretical TDE rate estimates. We calculate the optical TDE luminosity function and we find a steep power-law relation dN/dLg ∝ Lg−2.36±0.16.